Crossroads at sea: Escalating conflict in a marine protected area in Malta. (31st August 2018) - Said, Alicia; MacMillan, Douglas; Campbell, Brian
Abstract: This article illustrates how the creation of a Marine Protected Area (MPA) in Malta is failing to adequately include stakeholders in the configuration of conservation targets and measures, leaving local fishers increasingly disempowered. Through a series of interviews and long-term participatory observation, it has been found that the leaders who represent local fishers are failing to communicate the MPA process to their community. Instead, they are using their position in the MPA negotiations to subjugate and silence the fishing community in general and trammel netters in particular. Moreover, in their support for the MPA, these community leaders reproduce the state's conservation discourse to pressure authorities to ban trammel net fishing, with whom they tend to be in competition. It is concluded that the state's narrow focus on ecology, the tight deadlines set out in the EU Habitats Directive, and the misrepresentation of the fishers, has characterised the process of creating this MPA. If artisanal livelihoods are not protected by conservation policies, fishers may regard conservation as a threat to their way of life, and resist policy measures. This compromises conversation efforts and can make the enforcement of the MPAs more expensive. This paper recommends a revision of the community consultation policies of the MPA to allow broader and more representative participation from the local community by encouraging engagement throughout the process as part of a consensual approach to effective marine conservation.